Catalysts of self-assembled Pt@CeO2−δ-rich core–shell nanoparticles on 3D ordered macroporous Ce1−xZrxO2 for soot oxidation: nanostructure-dependent catalytic activity. Issue 13 (21st March 2017) - Wei, Yuechang; Jiao, Jinqing; Zhang, Xindong; Jin, Baofang; Zhao, Zhen; Xiong, Jing; Li, Yazhao; Liu, Jian; Li, Jianmei
Abstract : Nanocatalysts of 3DOM Pt@CeO2− δ -rich/Ce1− x Zr x O2 with a high density of oxygen vacancies show super catalytic performance for soot oxidation. Abstract : The catalytic performance in heterogeneous catalytic reactions consisting of solid reactants is strongly dependent on the nanostructure of the catalysts. Metal-oxides core–shell (MOCS) nanostructures have potential to enhance the catalytic activity for soot oxidation reactions as a result of optimizing the density of active sites located at the metal–oxide interface. Here, we report a facile strategy for fabricating nanocatalysts with self-assembled Pt@CeO2− δ -rich core–shell nanoparticles (NPs) supported on three-dimensionally ordered macroporous (3DOM) Ce1− x Zr x O2 via the in situ colloidal crystal template (CCT) method. The nanostructure-dependent activity of the catalysts for soot oxidation were investigated by means of SEM, TEM, H2 -TPR, XPS, O2 -isothermal chemisorption, soot-TPO and so on. A CeO2− δ -rich shell on a Pt core is preferentially separated from Ce1− x Zr x O2 precursors and could self-assemble to form MOCS nanostructures. 3DOM structures can enhance the contact efficiency between catalysts and solid reactants (soot). Pt@CeO2− δ -rich core–shell nanostructures can optimize the density of oxygen vacancies (Ov ) as active sites located at the interface of Pt–Ce1− x Zr x O2 . Remarkably, 3DOM Pt@CeO2− δ -rich/Ce1− x Zr x O2 catalysts show super catalytic performance and strongly nanostructure-dependent activity for soot oxidation in the absence of NO and NO2 . For example, the T 50 of the 3DOM Pt@CeO2− δ -rich/Ce0.8 Zr0.2 O2 catalyst is lowered down to 408 °C, and the reaction rate of the 3DOM Pt@CeO2− δ -rich/Ce0.2 Zr0.8 O2 catalyst (0.12 μmol g −1 s −1 ) at 300 °C is 4 times that of the 3DOM Pt/Ce0.2 Zr0.8 O2 catalyst (0.03 μmol g −1 s −1 ). The structures of 3DOM Ce1− x Zr x O2 -supported Pt@CeO2− δ -rich core–shell NPs are decent systems for deep oxidation of solid reactants or macromolecules, and this facile technique for synthesizing catalysts has potential to be applied to other element compositions.